The Research of Adaptive Data Desensitization Method Based on Middle Platform. (18th August 2022) - Wang, Jijun; Xu, Mingsheng; Lu, Kang
Abstract : With the popularization of Middle Platform characterized by data aggregating and governance, the security protection of data is paying more and more attention, and the data desensitization technology is widely used. In order to solve the high threshold for use, high customization, and lack of stability caused by conventional data desensitization methods, a desensitization strategy configuration system based on desensitization intensity and desensitization algorithm weight was established. The methods of reidentification risk assessment and information security attribute assessment were used to classify and quantify configuration items, and then, an adaptive desensitization strategy configuration method was proposed which not only simplifies the configuration process but also provides reliable desensitization data flexibly and stably for application requirements. It is beneficial to the development of an intelligent automatic data desensitization system.